UTILITY MODEL, TECHNOLOGICAL MATURITY, AND DUAL USE IN THE BRAZILIAN DEFENSE INDUSTRIAL BASE: AN ANALYSIS OF PATENT BR 202014017157-1 IN LIGHT OF TRL - Blaskievicz, Daniel Galrão de França; de Aquino Filho, José Seixas; Caracas Neto, Roberto Augusto; da Silva, Elizabeth Ferreira; Winter, Eduardo (Seven Editora, 2026)
This study analyzes intellectual property (PI) management in the Brazilian Defense Industrial Base (BID), focusing on the underutilization of the Utility Models (MU) compared to invention patents. The main objective is to characterize patent BR 202014017157-1, related to a gas-powered pistol modification, a component of a shooting simulator, from the perspective of technological maturity (TRL) and dual-use potential. Through a qualitative and documentary approach, the research demonstrates that the MU is the most suitable instrument for incremental innovations at intermediate readiness levels (TRL 4 to 6), positioning them close to practical application. The analyzed technology shows high strategic versatility, enabling cost reduction and increased safety in both military training and in civilian and recreational contexts. The analysis outlines three strategic scenarios for managing the asset: restrictive, focused on national autonomy and maximum protection of sensitive secrets; Partial Opening, aimed at achieving scale and licensing to civilian markets and selected international partners; and hybrid, which combines patent protection with trade secrets to allow selective technical cooperation. It is concluded that the full exploitation of this asset requires robust institutional governance to manage power asymmetries in negotiations and maximize technological spillovers. Strengthening the BID depends on integrating the MU into mission-oriented incrementalism, ensuring sovereignty and industrial competitiveness.